2015
DOI: 10.1136/bcr-2014-208658
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged duration of transbrachial intra-aortic balloon pump as bridge to heart transplantation

Abstract: SUMMARYWe describe a case demonstrating the quality of life (QOL) benefit and safety of using a transbrachial approach for insertion of an intra-aortic balloon pump (IABP) in a patient awaiting cardiac transplantation. A 68-year-old man with ischaemic cardiomyopathy was admitted to our cardiac intensive care unit to await the availability of a suitable donor organ for orthotopic heart transplant. An IABP was needed for haemodynamic support due to cardiogenic shock. Since the patient did not want to be committe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Smith et al 11 reported a case of a patient with ICM who received a percutaneously inserted left brachial IABP for BTT. The patient was weaned from the IABP in 10 days without any complications and received a heart transplant 3 weeks later.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Smith et al 11 reported a case of a patient with ICM who received a percutaneously inserted left brachial IABP for BTT. The patient was weaned from the IABP in 10 days without any complications and received a heart transplant 3 weeks later.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Heart transplantation is an effective method to treat end‐stage heart diseases . The main factor restricting heart transplantation is the lack of suitable donors .…”
mentioning
confidence: 99%